How Climate Change Will Alter the Distribution of Suitable Dendrobium Habitats - Tang, Xinggang; Yuan, Yingdan; Zhang, Jinchi (Frontiers in Ecology and Evolution, 2020)
To protect endangered species and restore their habitats, it is important to be able to predict their potential geographic distributions. The Dendrobium plant is important in traditional Chinese medicine, but urban expansion and over-exploitation have led to a decrease of Dendrobium resources. To achieve sustainable development of Dendrobium resources, here we systematically analyze the spatial and temporal distribution of two Dendrobium species, D. moniliforme and D. nobile. Maximum entropy modeling (MaxEnt) and the ArcGIS geographic information system were used to predict the distribution of suitable habitats for these Dendrobium species, both presently and in the future, under various greenhouse gas emission models. We found that D. moniliforme and D. nobile are widely distributed in the south of China (Anhui, Guangdong, Jiangxi, and Hunan provinces). Worldwide, Japan and North Korea were identified as major distribution areas for D. moniliforme and D. nobile. Based on the MaxEnt model, the mean diurnal range and the minimum temperature of the coldest month were identified as the most signiﬁcant bioclimatic variables controlling the distribution of D. moniliforme and D. nobile. Future climate change will likely result in an increase of suitable habitat area for D. moniliforme (by around 16%), and decrease for D. nobile (by around 1-10%), but climate change is unlikely to have much impact on the distribution of suitable habitats for D. moniliforme and D. nobile in Japan and North Korea. Based on our findings, measures should be taken to protect these precious medicinal plant resources, and the sites used for the artificial cultivation of Dendrobium will need to shift as the climate changes.